2001
DOI: 10.1016/s0014-5793(01)02278-5
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of peroxisome proliferator‐activated receptor‐γ gene expression by sphingomyelins

Abstract: We recently demonstrated that the sphingomyelin (SM) content of adipocyte membranes was negatively correlated with the expression of peroxisome proliferator-activated receptor-Q Q (PPARQ Q) in the subcutaneous adipose tissue of obese women with variable degrees of insulin resistance. We have now investigated whether SM really does have an impact on the expression of PPARQ Q in 3T3-F442A adipocytes. Adding SM to the culture medium for 24 h caused a significant increase in SM content of adipocyte membranes and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…We previously reported that excess sphingomyelin in the membranes of 3T3-F442A adipocytes decreased PPARγ expression [ 14 ] and that the SM/CHOL ratio represented an important determinant of glucose transport [ 32 ] in preadipocytes. These findings led us to further study the effect of SM overabundance on the expression of the transcription factor SREBP because SREBP-1 is a key regulator of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that excess sphingomyelin in the membranes of 3T3-F442A adipocytes decreased PPARγ expression [ 14 ] and that the SM/CHOL ratio represented an important determinant of glucose transport [ 32 ] in preadipocytes. These findings led us to further study the effect of SM overabundance on the expression of the transcription factor SREBP because SREBP-1 is a key regulator of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SM may affect cellular signaling. Membrane SM was negatively related to the transcription factor peroxisome proliferator–activated receptor-γ (PPARγ) mRNA levels in subcutaneous adipocytes of obese insulin-resistant women [ 13 ] and in SM-enriched 3T3-F442A adipocytes [ 14 ]. Recently, adipose PPARγ has been identified as an essential mediator of lipid and glucose homeostasis and of whole body insulin sensitivity [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, sphingolipids have been shown to antagonize the effects of PPAR-␥. Specifically, sphingomyelin downregulates PPAR-␥ gene expression in 3T3-F442 adipocytes and is an independent predictor of insulin resistance in obese women (184,185). Ceramide has similarly been shown to inhibit PPAR-␥ expression (186).…”
Section: Thiazolidinediones Glucose Transport Corticosteroids and mentioning
confidence: 99%